No + Municipalization. Teaching Resistance to Transfers of Public Schools. Chile, 1986 ["No + Municipalización". la Resistencia Docente a Los Traspasos de Escuelas Públicas. Chile, 1986 - Alvarez-Vallejos, R; Matamoros-Fernandez, C (Ariadna Ediciones, 2021)
During the 1980s, the Chilean civil-military dictatorship carried out neoliberal educational reforms that profoundly modified the working conditions of teachers, especially due to the transfer of establishments from the State to the municipalities. During the first transfer period, there were some activist demonstrations, but only in 1986 were massive resistances to those policies executed. These practices did not represent a homogeneous opposition through the defense of an alternative educational policy to the official one, but rather it was an opposition guided by the political times of the conjuncture, where some sectors began to positively evaluate a municipalized education system. Based on the analysis of different backgrounds, in this work we seek to critically analyze, from a historical and political perspective, the responses presented by the various organizations and political forces of the teachers in front of the municipality. © 2021 Ariadna Ediciones. All rights reserved.